Combining paid work and family care : Policies and experiences in international perspective - Kröger, Teppo; Yeandle, Susan (The Policy Press, 2013)
Highlighting what can be learned from individual experiences, the book analyses the changing welfare and labour market policies which shape the lives of working carers in Finland, Sweden, Australia, England, Japan and Taiwan.